IDENTIFICATION OF SUBSURFACE STRUCTURES IN SOUTH BENGKULU MANNA CITY BASED ON THE MASW METHOD - Saragih, Ronni Samuel; Refrizon, Refrizon; Hadi, Arif Ismul (Universitas Mataram, 2023)
South Bengkulu is one of the regencies in Bengkulu Province which is in an area of active tectonic plate activity, namely the India-Australia and Eurasian plates so it is prone to earthquakes. The City of Manna continues to carry out developments so that it requires various information for urban and regional planning, especially information on subsurface rock structures. This study aims to determine the structure of rock layers based on shear wave velocity (Vs), Poisson ratio, shear modulus and Young's modulus in Manna City. This research was conducted using the Multichannel Analysis of Surface Wave (MASW) method at 12 measurement stations. The tool used is the PASI 16S24-P seismograph. Data processing to produce a 1D model is WinMASW 5.0 Professional Software and to display 3-D data Voxler software is used based on the value of Vs. Then do the calculation to get the value of Vs30. Â From the results of the Vs30 value in the study area, it shows that the Manna City area consists of 4 rock types including soft soil (SE), stiff soil (SD), very dense soil and soft rock (SC) and rock (SB) rock types. The highest layering value of shear wave velocity (Vs) is at the fourth point with a value of Vs 386-1263 m/s, Poisson ratio 0.40-0.35, shear modulus 298-3652 MPa and Young's modulus 804-9430 MPa at a depth of 4.4 -30 meters. While the smallest value is at the sixth location point with a value of Vs 180-474 m/s, Poisson ratio 0.40-0.30 shear modulus 60-461 MPa, and Young's modulus 168-1.243 MPa at a depth of 2.6-30 meters.